Delhi, then & now. - Kapoor, Pramod; Gupta, Narayani; Bobb, Dilip (New Delhi Lustre Press, Roli Books, 2007)
A two part illustrated narrative on Delhi, India's capital city; authored separately by Narayani Gupta and Dilip Bobb, with photo research & editing by Pramod Kapoor.
Delhi, then / Narayani Gupta -- Delhi, now / Dilip Bobb.
Bound back to back and inverted.
Keywords: Delhi (India) -- Pictorial works; New Delhi (India) -- Pictorial works; Delhi (India) -- History; New Delhi (India) -- Social life and customs